Genetic kinship of tongkat langit banana (Musa troglodytarum L.) from Moluccas based on rbcL gene sequence - Hiariej, Adriana; Arumingtyas, Estri Laras; Widoretno, Wahyu; Azrianingsih, Rodliyati (The Indian Journal of Genetics and Plant Breeding, 2016)
The present study was conducted to investigate the genetic kinship of tongkat langit banana population from Moluccas which was out-grouped into Musa fehi, Ensete glaucum, Ensete superbum dan Ensete ventricosum (NCBI). The results of phylogenetic analysis showed that tongkat langit banana and Musa fehi formed sub-clade I with similarity value of 99-100%. Ensete genus formed clade II with similarity value of 98-99%.